2019
DOI: 10.1037/pspa0000143
|View full text |Cite
|
Sign up to set email alerts
|

When and why people misestimate future feelings: Identifying strengths and weaknesses in affective forecasting.

Abstract: People try to make decisions that will improve their lives and make them happy, and to do so, they rely on affective forecasts-predictions about how future outcomes will make them feel. Decades of research suggest that people are poor at predicting how they will feel and that they commonly overestimate the impact that future events will have on their emotions. Recent work reveals considerable variability in forecasting accuracy. This investigation tested a model of affective forecasting that captures this vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(72 citation statements)
references
References 42 publications
4
67
0
1
Order By: Relevance
“…This study was part of a larger investigation of the accuracy with which people forecast different features of their emotional experience. Hypotheses for the larger project are addressed in another paper (Lench et al, 2019). The main hypotheses for the current investigation were described in a published review (Levine et al, 2018) but analyses were not preregistered.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was part of a larger investigation of the accuracy with which people forecast different features of their emotional experience. Hypotheses for the larger project are addressed in another paper (Lench et al, 2019). The main hypotheses for the current investigation were described in a published review (Levine et al, 2018) but analyses were not preregistered.…”
Section: Methodsmentioning
confidence: 99%
“…First, participants both predicted and remembered the intensity of their feelings about Trump's election fairly accurately. Past research has also shown high accuracy when people predict or remember the intensity of their feelings about events (e.g., Doré et al, 2016;Kaplan et al, 2016;Lench et al, 2019;Levine et al, 2012). Far less accuracy is found when people predict or remember their general emotional experience, a judgment that encompasses multiple features of emotion including intensity, duration, and mood (e.g., Wilson et al, 2000).…”
Section: Similarities Found Between Predicted and Remembered Emotionmentioning
confidence: 99%
“…This second prompt specifically references the emotion-eliciting event and is consistent with wording in affective forecasting measures (e.g., Kermer et al, 2006;Wilson & Gilbert, 2003, 2005Wiener et al, 2014). To address the methodological issues that Lench et al (2019) raised, all participants completed measures that asked them how the policy 6 HOLLOWAY AND WIENER (affects/will affect) their overall mood, and how frequently they will think about the policy (right now/if the government pursues it). By asking about the effects of the policy, itself, this study avoided methodological concerns in the affective forecasting literature pertaining to question wording biasing results (Lenchet al, 2019).…”
Section: Emotion Forecastingmentioning
confidence: 99%
“…Recently, some authors have raised concerns about the usual means of measuring and interpreting affective forecasting inaccuracies, challenging the significance and validity of the intensity bias ( Lench et al, 2019 ; Levine et al, 2012 , 2013 ; Mathieu & Gosling, 2012 ).…”
Section: Different Approaches In the Study Of Affective Forecastingmentioning
confidence: 99%